Weaving sociocultural change and cognitive development together - Carmiol Barboza, Ana María (2007)
In her book Weaving Generations Together, Patricia Greenfield presents an account of the nature and course of human development that suggests a tight relationship with sociocultural change. During two extensive stays in the Zinacantec Mayan hamlet of Nabenchauk, Mexico, in 1969–70 and 1991, Greenfield studied weaving, the typical activity of Mayan women, and developed a long-term project spanning two generations of Zinacantec mothers teaching their daughters how to weave. The results of this project are documented in the book, initially developed as a catalog for a museum exhibition; as well as in multiple scientific reports by the author and her collaborators (e.g., Childs & Greenfield, 1980; Greenfield, 2000; Greenfield, Maynard, & Childs, 2000; Maynard & Greenfield, 2003; Maynard, Greenfield, & Childs, 1999). Relying on empirical data accompanied by beautiful photographic work by Lauren Greenfield, the book selects the following foci for study: the ontogenesis of weaving as a product of biology and culture; the transformations in weaving apprenticeship and in the cognitive and creative processes involved in it between 1969–70 and 1991; and the role of sociocultural change in these transformations.